Monopotassium maleate salt stabilizes SnO2 colloid solution for efficient perovskite solar cells - Xiaoxuan Liu; Derun Sun; Huande Sun; You Gao; Fumeng Ren; Rui Chen; Xin Meng; Siqi Zhang; Wei Chen; Zonghao Liu (APL Energy)
Constructing a high-quality SnO2 electron transport layer plays an important role in the fabrication of high-performance n–i–p perovskite solar cells (PSCs). Herein, we report a SnO2 modification strategy by using monopotassium maleate (MPM) salt to functionalize the SnO2 nanocrystals. It is demonstrated that MPM can effectively inhibit the agglomeration of SnO2 nanocrystals, thereby improving the conductivity and electron mobility of SnO2 and passivating the defects at the buried SnO2/perovskite interface. Meanwhile, the interfacial energy level alignment between SnO2 and the perovskite layer is improved. With MPM-modified SnO2, the power conversion efficiency (PCE) of the PSCs is substantially improved from 21.8% to 24.1%. In addition, a noteworthy PCE of 19.8% is achieved for perovskite solar modules with an active area of 10.25 cm2. The unencapsulated devices maintain 90% of the initial PCE after 1000 h of continuous tracking testing at the maximum power point in a nitrogen atmosphere at room temperature.